Edukasi Sistem Managemen Keselamatan dan Kesehatan Kerja (SMK3) Radiasi di Instalasi Radiologi RS Bhayangkara Semarang - Suraningsih, Nanik; Rosidah, Siti; Jamil, Masfufatun (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
7 components of the Radiation Safety Management System (Radiation SMK3) that must be applied in the use of radioactive substances or other radiation sources. Implementation at the Bhayangkara Hospital Radiology Installation in Seamarang contained components that were not optimal, including storage and education and training. The aim of this activity is to increase the knowledge of radiation officers about the 7 components of radiation SMK3. The methods used are lectures and discussions. The results of community service activities for radiation workers are increased knowledge and understanding of the counseling material provided. This can be seen from the discussion and question and answer sessions given to the audience who were able to respond and answer the questions given well according to the material provided by the service team.